Quantifying Biophoton Emissions From Human Cells Directly Exposed to Low-Dose Gamma Radiation. Issue 2 (18th May 2020) - Cohen, Jason; Vo, Nguyen T. K.; Chettle, David R.; McNeill, Fiona E.; Seymour, Colin B.; Mothersill, Carmel E.
Biophoton emission leading to bystander effects (BEs) was shown in beta-irradiated cells; however, technical challenges precluded the analysis of the biophoton role in gamma-induced BEs. The present work was to design an experimental approach to determine if, what type, and how many biophotons could be produced in gamma-irradiated cells. Photon emission was measured in HCT116 p53 +/+ cells irradiated with a total dose of 22 mGy from a cesium-137 source at a dose rate of 45 mGy/min. A single-photon detection unit was used and shielded with lead to reduce counts from stray gammas reaching the detector. Higher quantities of photon emissions were observed when the cells in a tissue culture vessel were present and being irradiated compared to a cell-free vessel. Photon emissions were captured at either 340 nm (in the ultraviolet A [UVA] range) or 610 nm. At the same cell density, radiation exposure time, and radiation dose, HCT116 p53 +/+ cells emitted 2.5 times more UVA biophotons than 610-nm biophotons. For the first time, gamma radiation was shown to induce biophoton emissions from biological cells. As cellular emissions of UVA biophotons following beta radiation lead to BEs, the involvement of cellular emissions of the same type of UVA biophotons in gamma radiation-induced BEs is highly likely.